Aplikasi Sistem Automated Essay Scoring untuk Jawaban Soal Ujian dengan Menerapkan Algoritma Jaro-Winkler - Harefa, Krisnawati; Lubis, Abdul Jabbar (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2022)
ABSTRACK In its development, the essay exam features become an obstacle, because the increase in the number of students and the number of examinations results in the teacher taking the time to assess the answers to the exam questions. In general, the answer correction system for essay answers is done manually, so the use of e-learning and without e-learning in terms of time efficiency there is no difference. Therefore, an automatic assessment system is needed on essay examinations to accelerate the process of evaluating student answers. Automated essay scooring is an automatic scoring system by comparing two answers and then calculating the results of a comparison using an existing algorithm. One algorithm used is the Jaro-Winkler Distance algorithm, which is to measure the similarity between two strings. In this research, an automated essay scoring system integration is based on the Jaro-Winkler Distance algorithm, so that with an automated scoring essay system, it can help the teacher in the essay answer correction process. The results of the system testing show, the assessment of the answers generated by the system is influenced by whether or not there is a key term in the answer sentence. The more different the number of words in a sentence between teacher and student, the smaller the resulting value. If a student's answer sentence has a key term distribution which is the same as the teacher's answer key then the resulting value is also higher.